Organisational Culture and Transformational Leadership Style Affect Employee Performance with Innovative Work Behaviour as Mediation Variables - Widianingsih, Dewi; Christa, Usup Riassy; Harinie, Luluk Tri (SENTRALISASI, 2024)
This study aims to empirically analyze the influence of organizational culture, transformational leadership style, and innovative work behaviour on employee performance, as well as investigate the mediating effect of innovative work behaviour on the relationship between organizational culture and transformational leadership style on employee performance in the Archives and Libraries Office of North Barito Regency.The research method used is an explanatory quantitative approach with data collection using survey methods. The population in this study were all employees, except for the Head of the Archives and Libraries Office of North Barito Regency, which totalled 46 (forty-six) employees, both civil servants and honorary staff. The sampling technique used purposive sampling and obtained a sample of 43 Archives and Libraries Office employees of North Barito Regency—data analysis using SPSS and Smart PLS statistical applications. The results of the research in this study can be concluded (1) Organizational Culture has a positive and significant effect on employee performance; (2) The transformational leadership style has a positive and significant effect on employee performance; (3) Organizational Culture has no significant effect on innovative work behaviour; (4) The transformational leadership style has no significant effect on innovative work behaviour; (5) Innovative work behaviour has a positive and significant effect on employee performance; (6) Innovative work behaviour has not been able to mediate the influence of organizational culture on employee performance; (7) Innovative work behaviour has not been able to mediate the effect of transformational leadership style on employee performance.